Renta hipoteczna i odwrócona renta hipoteczna jako formy finansowania ubezpieczenia ryzyka niedołęstwa starczego - Więckowska, Barbara (Mortgage Annuity and Its Forms in Financing the Old-Age Infirmity Insurance, 2006)
The ageing society and the changes in modern family model, often termed "a silent revolution" both contribute to gradual increase of importance of the old-age infirmity. Simultaneously, they are also related to growing problems with the long-term care of infirmed elderly persons. The crucial issues become how to finance the long-term care and how to distribute the burden of managing this risk between the state and households. More and more often the postulates emerge for defining the standard level of social security in the area of the long-term care and for preparing additional financial resources by introducing private means into the long-term care system. The optimal solutions seem to be voluntary old-age infirmity insurance (long-term care insurance). Since usually the biggest financial assets possessed by the elderly is real-estate (house, apartments), some insurance solutions have been presented. Such arrangements finance the insurance contributions out of the real estate value. The paper presents two tools used in financing the voluntary old-age infirmity insurance: mortgage annuity and reverse mortgage annuity. These instruments are typical for the old-age infirmity insurance offered principally to persons who reached their retirement age. This group can be described as asset reach and cash poor. Therefore, their capacity to pay up the insurance premium is limited. The insurance tools described in the paper offer an actual time smoothing of consumption function so, consequently, one can speak of "a full usage of lifetime savings".
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 178-187